Role of vascular endothelial growth factor in the pathophysiology of nonalcoholic steatohepatitis in two rodent models. Issue 5 (14th March 2013) - Coulon, Stephanie; Legry, Vanessa; Heindryckx, Femke; Van Steenkiste, Christophe; Casteleyn, Christophe; Olievier, Kim; Libbrecht, Louis; Carmeliet, Peter; Jonckx, Bart; Stassen, Jean‐Marie; Van Vlierberghe, Hans; Leclercq, Isabelle; et al.
Abstract: The pathophysiology of nonalcoholic steatohepatitis (NASH) should be approached as a multifactorial process. In several stages of NASH, a link between disease progression and hepatic microvasculature changes can be made. In this study we investigated the role of angiogenesis in two mouse models for NASH, and the effect of a preventive and therapeutic antiangiogenic treatment in a diet‐induced mouse model for NASH. Protein and RNA levels of angiogenic and inflammatory factors were significantly up‐regulated in the liver of C56BL/6 and db/db mice with NASH at different timepoints. To examine the effect of angiogenic factors on the disease progression of NASH, a prevention and treatment study was set up, blocking the placental growth factor (PlGF) or vascular endothelial growth factor receptor 2 (VEGFR2). Our study showed that treatment prevents the progression of NASH by attenuating steatosis and inflammation, both in a preventive and therapeutic setting, thereby confirming the hypothesis that angiogenic factors play an early role in the disease progression from steatosis to NASH. Anti‐PlGF (αPlGF) did not significantly improve liver histology. Vascular corrosion casting showed a more disrupted liver vasculature in mice with NASH compared to controls. Treatment with αVEGFR2 showed an improvement of the liver vasculature. Moreover, fat‐laden primary hepatocytes treated with αVEGFR2 stored significantly less lipids. Conclusion: Our results demonstrate that there is an increased expression of angiogenic factors in the liver in different mouse models for NASH. We found that VEGFR2 blockage attenuates steatosis and inflammation in a diet‐induced mouse model for NASH in a preventive and therapeutic setting. Our findings warrant further investigation of the role of angiogenesis in the pathophysiology in NASH. (HEPATOLOGY 2013)